(untitled) (Journal of Engineering, 2022)
The printed circuit heat exchanger is a plate type heat exchanger with a high performance and compact size. Heat exchangers such as this need a unique form of bonding and other techniques to be used in their construction. In this study, the process of joining plates, diffusion bonding, was performed and studied. A special furnace was manufactured for bonding purposes. The bonding process of copper metal was carried out under specific conditions of a high temperature up to 700 oC, high pressure of 3.45 MPa, and in an inert environment (Argon gas) to make tensile samples. The tensile samples are cylindrical shapes containing groves representing the flow channels in the printed circuit heat exchanger and checking their tensile strength in addition to the standard shape of the tensile specimen to check the yield and ultimate strength of the copper. A higher tensile strength was obtained for diffusion bonded specimens than the yield strength of copper, up to 1.35 times the copper yield strength. The tensile strength decreases with the increase in the number of groves and the decrease in the distance between one grove and another. This is because the stress is concentrated in the sharp corners. A prototype heat exchanger of two plates and a header to be tested for its compressive strength was also manufactured. The results showed that the bond bears an air pressure of up to 8 bar without fail. It was also found to withstand a hydraulic pressure of up to 60 bar until it reached failure.